The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0004-282x2009000200019
|View full text |Cite
|
Sign up to set email alerts
|

Early shunt complications in 46 children with hydrocephalus

Abstract: -Objective: To determine the causes of early shunt complications in 46 children with hydrocephalus. Method: A retrospective study was conducted on 46 children submitted to ventriculoperitoneal shunt surgery between February 2005 and February 2007. Results: Thirteen (28%) patients presented complications, which were due to infection in 9 (69%) and to malfunction of the shunt system in 4 (31%).The mean number of surgical procedures performed on patients who presented complications was 2.8 per patient, with a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 15 publications
(22 reference statements)
2
26
1
1
Order By: Relevance
“…Factors including premature birth, occurrence of the first VPSI at a young age, congenital conditions such as meningomyelocele, post-hemorrhagic hydrocephalus, higher number of previous shunt infections, and the development of postoperative CSF leakage increase the risk of shunt infection (4,6,7,18,25). In this study, we found that children with VPSI in the first 3 months or with premature birth had a greater rate of shunt infections (high hospitalization coefficient) and higher treatment costs (high cost coefficient).…”
Section: Kanik a Et Al: Aspects Of Vps-related Infectionsmentioning
confidence: 55%
See 1 more Smart Citation
“…Factors including premature birth, occurrence of the first VPSI at a young age, congenital conditions such as meningomyelocele, post-hemorrhagic hydrocephalus, higher number of previous shunt infections, and the development of postoperative CSF leakage increase the risk of shunt infection (4,6,7,18,25). In this study, we found that children with VPSI in the first 3 months or with premature birth had a greater rate of shunt infections (high hospitalization coefficient) and higher treatment costs (high cost coefficient).…”
Section: Kanik a Et Al: Aspects Of Vps-related Infectionsmentioning
confidence: 55%
“…Shunt infections are caused by previous CSF infections or occur more generally due to skin contamination during surgical procedures (4,14). The surgeon's ability, speed, and experience; the timing of surgery; and the operating room conditions are controversial subjects in terms of the risk of The coefficient of cost…”
Section: Kanik a Et Al: Aspects Of Vps-related Infectionsmentioning
confidence: 99%
“…VP shunt infection rates in pediatric patients have been reported to range from 8-20% 22,23) , depending on factors such as age, immune status, and comorbidities 5) . In pediatric patients, hemorrhage is less common than in adults, and brain tumors are the main cause for hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the parenteral vancomycin treatment for more than 2 weeks with appropriate serum drug levels (15-20 g/mL), the CSF was not sterilized and CoNS con μ -tinued to grow from EVD samples. Rifampin (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) mg/kg/day) was added to the therapy and the CSF culture finally became negative after this combination therapy without complications (9 days and 15 days of combination therapy, respectively). The EVDs were removed and new VP shunts were inserted.…”
Section: Diagnosis Of Vp Shunt Infections In Children Ismentioning
confidence: 99%
“…2,8,26,32,37,[47][48][49] At present, there are several publications addressing pediatric VPS failure and/or its associated complications. However, we note that the majority of such literature tends to focus on early complicationsusually where the VPS fails within 1 or 2 years postoperatively.…”
Section: Neurosurg Focus 41 (5):e7 2016mentioning
confidence: 99%